2019
DOI: 10.1016/j.ensci.2019.100211
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 10 (SCA10): Mutation analysis and common haplotype based inference suggest its rarity in Indian population

Abstract: HighlightsGenetic screening of SCA10 in large cohort of Indian SCA patients.Estimation of at-risk haplotype using population genetics approach in south Asians.Suggestive rarity of SCA10 in the Indian Population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Anjanappa et al, 2019* [85] B a n g a l o r e 3 8 --1 8 ------Goel et al, 2019 [86] 4 6 1 --------reported with varying disease progression. [66] Early onset of the spinocerebellar ataxia has also been known to be associated with large CAG expansion mutations in respective genes.…”
Section: Discussionmentioning
confidence: 99%
“…Anjanappa et al, 2019* [85] B a n g a l o r e 3 8 --1 8 ------Goel et al, 2019 [86] 4 6 1 --------reported with varying disease progression. [66] Early onset of the spinocerebellar ataxia has also been known to be associated with large CAG expansion mutations in respective genes.…”
Section: Discussionmentioning
confidence: 99%